Pengembangan Media Pembelajaran Flipbook Kisah Keteladanan Walisongo untuk Meningkatkan Minat Belajar Siswa di MTsN 1 Jombang - Anggraeni, Nisa Lailatul; Rahmawati, Rina Dian (Lembaga Yasin AlSys, 2025)
This study aims to design and develop learning media in the form of flipbooks and test their feasibility, practicality, and readability on the material of the Walisongo Exemplary Stories at MTs Negeri 1 Jombang. This study uses the Research and Development (R & D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, evaluation. The study was conducted in November 2024 with its feasibility first tested by 1 material expert lecturer, 1 media expert lecturer, and grade IX students. Data were collected through interviews and assessment questionnaires from experts, teachers, and students. The results of the study revealed that the flipbook media provided significant results obtaining a score of 86% from material validation and 83% from media validation, both in the